Am nevoie de ajutor la matematică

Răspuns:
[tex](x - 1)^{2} = {x}^{2} - 2x + 1 \\ (x - 2) ^{2} = {x}^{2} - 4x + 4 \\ (x - 3) ^{2} = {x}^{2} - 6x + 9 \\ (x - 4) ^{2} = {x}^{2} - 8x + 16 \\ (x - 5) ^{2} = {x}^{2} - 10x + 25 \\ (2x - 1) ^{2} = {4x}^{2} - 4x + 1 \\ (4x - 1) ^{2} = {16x}^{2} - 8x + 1 \\ (5x - 1) ^{2} = {25x}^{2} - 10x + 1 \\ (2x - 3) ^{2} = {4x}^{2} - 2 \times 2x \times 3 + 9 = (2x - 1) ^{2} = {4x}^{2} - 12x + 9[/tex]
Explicație pas cu pas:
Am aplicat formula (a-b) ^2=a^2-2×a×b+b^2
Succes!!!
10)(x-1)²=x²-2*x*1+1²=x²-2x+1
11)(x-2)²=x²-2*x*2+2²=x²-4x+4
12)(x-3)²=x²-2*x*3+3²=x²-6x+9
13)(x-4)²=x²-2*x*4+4²=x²-8x+16
14)(x-5)²=x²-2*x*5+5²=x²-10x+25
15)(2x-1)²=(2x)²-2*2x*1+1²=4x²-4x+1
17)(4x-1)²=(4x)²-2*4x*1+1²=16x²-8x+1
18)(5x-1)²=(5x)²-2*5x*1+1²=25x²-10x+1
19)(2x-3)²=(2x)²-2*2x*3+3²=4x²-12x+9